EFEKTIVITAS PELAKSANAAN MEDIASI MENURUT PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2016 DALAM PERKARA WANPRESTASI DI PENGADILAN NEGERI SINGARAJA - Angraini, Betari Anggi; Dantes, Komang Febrinayanti D; Setianto, Muhamad Jodi (Universitas Pendidikan Ganesha, 2024)
This study aims to examine and analyze the effectiveness of the mediation of civil cases by the panel of judges of the Singaraja District Court based on perma no. 1 of 2016. The purpose of this thesis is to determine the implementation of mediation of civil cases in the Singaraja District Court, to understand the opportunities and obstacles of mediation in the Singaraja District Court as well as to analyze the effectiveness of mediation in the Singaraja District Court. The type of research used is Empirical Legal Research. The data and data sources used are primary data and secondary data The data collection techniques used are literature studies, interviews, and field studies. The sampling technique used is Purposive Sampling. The results of this study show that every mediation implementation in the Singaraja District Court is in accordance with the procedures written in perma no. 1 of 2016. Factors that can hinder the chances of success of a mediation in the Singaraja District Court are the lack of support of the litigants, parties do not attend after a summons is made, so that the obligation to resolve disputes through mediation cannot be resolved or carried out.the connection in this study is that judges in mediators at the Singaraja District Court can evaluate the implementation of mediation carried out in court. To the parties to the dispute or related to prioritize peace in resolving problems.